Structure of R&D capital expenditure and national total factor productivity - Juniours Marire (Cogent Economics & Finance, 2023)
This paper examines the relationship between the structure of R&D fixed capital spending, measured as the ratio of the private sector to public sector R&D capital expenditure, and national total factor productivity. It employs South African data for the period 1965 to 2019. This study employs the non-linear distributed lag modelling framework to cater for non-linearities in the relationship. The findings, first, suggest that the ratio of private sector to public sector R&D capital spending has a positive effect on total factor productivity. Second, the structure of R&D capital spending has large asymmetric effects on national total factor productivity, with negative changes dominating positive changes. Negative changes in the structure of R&D capital spending negatively influence total factor productivity, but positive changes have positive effects. Both in the short run and the long run, cumulative multipliers indicate that negative changes in the structure of R&D capital spending dominate positive changes by a very large margin. The findings imply that the private sector must become more dominant than the public sector in R&D capital spending in the national system of innovation.
Keywords: 330; <R&D capital expenditure; capital budget; non-linear autoregressive distributed lag model; techno-military regime; total factor productivity; white paper on science and technology